Dietary supplementation with soybean oil has not favored the tilapia growth in BFT tanks submitted to feeding restriction - Francisco Roberto dos Santos Lima; Marcos Luiz da Silva Apoliano; Davi de Holanda Cavalcante; Marcelo Vinícius do Carmo e Sá (Acta Scientiarum. Animal Sciences, 2023)
The present work aimed at assessing the possibility of compensating the notorious deficiencies of bioflocs in lipids by supplementing the tilapia commercial diet with soybean oil. In the positive control, there was no feeding restriction nor dietary supplementation with soybean oil. In the experimental treatments, the commercial diet was restricted by 25% over the positive control level. In the negative control tanks, there was feeding restriction and the artificial diet had no oil supplementation. In the experimental tanks, soybean oil was mixed daily with the commercial diet at the levels of 0.6%, 1.2 and 2.4%. Additionally, there were fed-restricted tanks that received a daily supplementation of 1.2% soybean oil mixed with dry molasses, and not with the commercial diet. In general, only the restriction of the commercial diet affected the water quality. The supplementation of the artificial diet with soybean oil up to 2.4% has not improved the proximate composition of bioflocs, nor the fish growth performance. It was concluded that the strategy of supplementing the Nile tilapia juveniles’ commercial diet with increasing levels of soybean meal, in BFT tanks submitted to 25%-feeding restriction, was not capable of avoiding the fish growth performance deterioration.